Contrast-induced acute kidney injury and mortality in ST elevation myocardial infarction treated with primary percutaneous coronary intervention. Issue 9 (1st November 2017) - Silvain, Johanne; Nguyen, Lee S; Spagnoli, Vincent; Kerneis, Mathieu; Guedeney, Paul; Vignolles, Nicolas; Cosker, Kristel; Barthelemy, Olivier; Le Feuvre, Claude; Helft, Gérard; Collet, Jean-Philippe; Montalescot, Gilles
Abstract : Objectives: Contrast-induced acute kidney injury (CI-AKI) is a common and potentially severe complication in patients with ST elevation myocardial infarction (STEMI) treated with primary percutaneous coronary intervention (pPCI). There is no consensus on the best definition of CI-AKI to identify patients at risk of haemodialysis or death. The objective of this study was to assess the association of CI-AKI, using four definitions, on inhospital mortality, mortality or haemodialysis requirement over 1-year follow-up, in patients with STEMI treated with pPCI. Methods: In this prospective, observational study, all patients with STEMI referred for pPCI were included. We identified independent variables associated with CI-AKI and mortality. Results: We included 1114 consecutive patients with STEMI treated by pPCI. CI-AKI occurred in 18.3%, 12.2%, 15.6% and 10.5% of patients according to the CIN, Acute Kidney Injury Network (AKIN), Risk, Injury, Failure, Loss of kidney function, and End-stage kidney disease (RIFLE) Modification of Diet in Renal Disease (MDRD) and RIFLE Chronic Kidney Disease - Epidemiology Collaboration (CKD-EPI) definitions, respectively. The RIFLE (CKD-EPI) definition was the most discriminant definition to identify patients at higher risk of inhospital mortality (27.1% vs 4.0%; adjusted OR 2.7 (95% CI 1.4 to 5.1), p=0.003), 1-year mortality (27.4% vs 6.6%; adjusted OR 2.8 (95% CI 1.5 to 5.3), p=0.002) and haemodialysis requirement at 1-year follow-up (15.6% vs 2.7%; adjusted OR 6.7 (95% CI 3.3 to 13.6), p=0.001). Haemodynamic instability, cardiac arrest, preexisting renal failure, elderly age and a high contrast media volume were independently associated with 1-year mortality. Of interest, contrast-media volume was not correlated to increase of creatininaemia (r=0.06) or decrease in estimated glomerular filtration rate (r=0.05) after percutaneous coronary intervention in our population. Conclusions: CI-AKI is a frequent and serious complication of STEMI treated by pPCI. The RIFLE definition is the most accurate definition to identify patients with CI-AKI at high risk of mortality or haemodialysis.